2004
DOI: 10.1016/j.ehj.2004.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognosis of subjects with Brugada-type ECG pattern in a young and middle-aged Finnish population

Abstract: The benign natural course of the patients with the "Brugada sign" suggests that in asymptomatic subjects without a family history of sudden cardiac death, type 2 or 3 Brugada ECG pattern is a normal variant rather than a specific predictor of life-threatening ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 21 publications
3
34
0
1
Order By: Relevance
“…In keeping with previous reports,4, 7, 9, 10, 21, 22 there was a male predominance among participants with BrS. In the present study, no SCD among participants with type 1 BrS and only 1 SCD among those with non–type 1 BrS was observed during the follow‐up period, which was consistent with previous community‐based studies,6, 8, 9, 12, 14 except for the Atomic Heart Study 11.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In keeping with previous reports,4, 7, 9, 10, 21, 22 there was a male predominance among participants with BrS. In the present study, no SCD among participants with type 1 BrS and only 1 SCD among those with non–type 1 BrS was observed during the follow‐up period, which was consistent with previous community‐based studies,6, 8, 9, 12, 14 except for the Atomic Heart Study 11.…”
Section: Discussionsupporting
confidence: 92%
“…The data from previous studies vary regarding prevalence and prognosis for patients with Brugada‐type ECG (BrS) because of different populations (eg, general population, office workers),4, 5, 6, 7, 8, 9 different ECG definitions,5, 6, 9, 10, 11, 12 relatively short‐term follow‐up,5, 6, 9, 10, 12, 13 or poorly defined SCD 5, 6, 7, 8, 10, 11, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…5,13,15) Junttila, et al 6) reported a ratio of 0.61% in 2479 young males aged between 18-30 years, and 0.55% in 542 individuals aged between 40-60 years. In Japan, the frequency in males has been reported to vary between 0.14-2.41% and 0.04% in females.…”
Section: )mentioning
confidence: 98%
“…Brugada sign frequency was reported to be 0.61% and 0.55% in 2 different age groups consisting of only males in Finland. 6) However, there are no data regarding the prevalence of Brugada syndrome and sign in Turkish populations. The frequency of 0.48% obtained in our study is similar to those found in other European countries, with the exception of one study reporting a frequency of 6.1%.…”
Section: Frequency Of Brugada Signmentioning
confidence: 99%
See 1 more Smart Citation